2011
DOI: 10.1111/j.1740-0929.2010.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and partial purification of a bacteriocin‐like substance produced by thermophilic Bacillus licheniformis H1 isolated from cow manure compost

Abstract: The production and partial characterization of bacteriocin-like substances (BLSs) produced by bacteria isolated from cow manure compost were investigated. Eight BLS producers, which exhibited inhibitory activity against pathogenic bacteria, were isolated from cow manure compost at different stages of the composting process. The pile temperature ranged from 9.1 °C to 73.2 °C. The BLSs showed thermostability, but the BLS producers were not thermostable except for the H1 producer. Thermophilic Bacillus lichenifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In addition to B. subtilis , B. licheniformis also has the ability to synthesize antimicrobial substances, such as surfactin (Pecci et al 2010; Sumi et al 2015). This antimicrobial substance shows antibacterial activity against a wide range of Gram-positive bacteria, such as Listeria monocytogenes and Methicillin-resistant S. aureus , but does not cause hemolysis or inhibit the growth of Gram-negative bacteria (Dischinger et al 2009; Abdel-Mohsein et al 2011). To date, the isoforms of surfactin and antibacterial activity in B. licheniformis have rarely been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to B. subtilis , B. licheniformis also has the ability to synthesize antimicrobial substances, such as surfactin (Pecci et al 2010; Sumi et al 2015). This antimicrobial substance shows antibacterial activity against a wide range of Gram-positive bacteria, such as Listeria monocytogenes and Methicillin-resistant S. aureus , but does not cause hemolysis or inhibit the growth of Gram-negative bacteria (Dischinger et al 2009; Abdel-Mohsein et al 2011). To date, the isoforms of surfactin and antibacterial activity in B. licheniformis have rarely been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Exported bacterial substances can fulfill different functions, B. licheniformis is known to secrete a number of different substances into the extracellular medium and this ability has been used in the fermentation industry for a long time. Many of these substances have also antifungal activity, such as peptide [ 15 , 17 ], biosurfactant [ 5 , 18 ], Chitinase [ 19 ], Laccase [ 20 ]. Many bacteriocins from Gram-positive bacteria, some of which are produced by B. licheniformis strains, have been isolated from buffalo rumen and the Amazon basin [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weight of F2 protein, differed clearly from other antifungal agents (enzymes, peptides and proteins) produced by B. licheniformis . B. licheniformis produces various antifungal substances with molecular masses ranging from 1.4 to 20 kDa [ 1 , 5 , 9 , 10 , 11 , 15 , 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that B. licheniformis can synthesize antimicrobial lipopeptides [ 33 , 34 ]. Surfactin, one of B. licheniformis -derived antimicrobial lipopeptides, exhibits antibacterial activity against a wide range of Gram-positive bacteria, such as Listeria monocytogenes and Methicillin-resistant S. aureus , but does not cause hemolysis [ 35 , 36 ]. Our previous findings have demonstrated that surfactin isolated from fermented products inhibits the growth of C. perfringens and B. hyodysenteriae [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%